Подземная гидросфера и геофлюидыy земной коры и верхней мантииy - Кудельский, А.В. (Геофизический журнал, 2017)
Схарактеризовано фізико-хімічний стан води і розсолів у різних термобаричних умовах земних надр, установлено дві групи геофлюїдних систем для води: субкритичні (T < 374 - 450 °С) інадкритичні (T > 374 - 450 °С), які разом з гідрогеологічною системою структурованих вод складають гідрофізичну, гідро- і флюїдогеологічну зональність літосфери. The physicochemical state of the water at various temperature and pressure conditions of the Earth's interior has been characterized. Two groups of geofluidic systems for water have been established: subcritical (T < 374 - 450 °C) and supercritical (T > 374 - 450 °C), which together with the hydrogeological system of structured waters constitute hydrophysical, hydro- and fluid-geological lithosphere zonation.